Dual mobility cups in total hip arthroplasty - De Martino, Ivan (Baishideng Publishing Group Inc, 2014)
Total hip arthroplasty (THA) is considered one of the most successful surgical procedures in orthopaedics. With the increase in the number of THAs performed in the world in the next decades, reducing or preventing medical and mechanical complications such as post-operative THA instability will be of paramount importance, particularly in an emerging health care environment based on quality control and patient outcome. Dual mobility acetabular component (also known as unconstrained tripolar implant) was introduced in France at the end of the 1970s as an alternative to standard sockets, to reduce the risk of THA dislocation in patients undergoing primary THA in France. Dual mobility cups have recently gained wider attention in the United States as an alternative option in the prevention and treatment of instability in both primary and revision THA and offer the benefit of increased stability without compromising clinical outcomes and implant longevity. In this article, we review the use of dual mobility cup in total hip arthroplasty in terms of its history, biomechanics, outcomes and complications based on more than 20 years of medical literature.